In vitro digestibility characteristics of octenyl succinic acid (OSA) modified starch with different amylose content. (30th January 2020) - Lopez-Silva, Madai; Bello-Perez, Luis A.; Castillo-Rodriguez, Victor M.; Agama-Acevedo, Edith; Alvarez-Ramirez, Jose
Abstract: The effect of amylose content in the in vitro digestibility of non-modified and OSA-modified corn starch was studied. Corn starches with different amylose content (waxy, normal and Hylon VII) were treated with 3% OSA solution. In vitro digestibility tests showed that OSA treatment reduced the fraction of fastly digestible starch, an effect that was more pronounced for cooked starch. The amylose content was negatively linked to the decrease of in vitro digestion. HPSEC analysis was conducted to gain insights on the effect of OSA-treatment on in vitro digestibility. The results showed an increase of the molecular weight of starch chains. Besides, the molecular weight increase was similar for amylose and amylopectin fractions. This suggests that OSA could be acting as a cross-linking agent between starch chains, reducing the susceptibility to amylolysis. Overall, OSA treatment induced the formation of more complex starch chains, offering more resistance for amylolytic reactions. Highlights: Effects of OSA treatment of corn starch were dependent on amylose content. OSA esterification decreased the mean molecular weight of amylose chains. OSA esterification increased in vitro SDS and RS fractions.